Deteksi Dini Masalah Kesehatan Mental pada Remaja dengan Self-Reporting Questionnaire (SRQ-29) - Rika Sarfika; Hema Malini; Nursyirwan Effendi; Putri Indah Permata; Ainul Fitria; Febi Sagitaria (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this community service activity is to carry out mental health screening as an effort to detect mental health problems in adolescents early. The method of implementing the activities consists of 3 stages: the preparation stage, the implementation of screening with the SRQ-29 instrument (Self-Reporting Questionnaire 29), and education. One hundred seventy-six teenage students in one of the Padang City State Senior High Schools participated in this activity. Adolescents who participated consisted of grades 10, 11, and 12. The results of these activities found that more than half of adolescents (56.8%) were identified as having symptoms of neurosis (anxiety and depression), more than half of adolescents (63.6%) were identified with psychotic symptoms, most of the adolescents (77.3%) were identified PTSD symptoms, and about 0.6% of adolescents were identified as using psychoactive substances. The results illustrate that most adolescents experience mental health problems in the form of anxiety and depression, psychotic, and PTSD symptoms that require further attention and treatment. For this reason, the attention and active participation of all parties, such as the government (education office, health office, schools) and families, overcome seriously adolescent mental health problems. Improving the function of guidance and counseling services (BK) in schools is very important. Counseling and scheduled mental health education can increase adolescent awareness and understanding of mental health.